The «AREOLA» system: a program shell for creating electronic encyclopedias - Bryzgalov, P.A. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2005)
A program shell for creating Internet-encyclopedias on various areas of knowledge is described.